Internet connectivity disruption in China (China) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in China. Data sourced from IODA.
Network Disruption Incident ID: CN-2026-0170. Severity: critical. Confidence: 75%